Toward strong, transparent and science-based dietary guidance: lessons learned from the Mediterranean Diet guideline development - Rossi, Laura; Gianfredi, Vincenza; Lezo, Antonella; Maggi, Stefania; Nucci, Daniele; Onder, Graziano; Silano, Marco; Troiano, Ersilia; Volpe, Massimo; Zanetti, Michela; Veronese, Nicola (Frontiers in Nutrition, 2025)
The Mediterranean Diet Guidelines (MDGs) represent a structured, evidence-informed effort to redefine and promote the Mediterranean Diet (MD) as a tool for health promotion and disease prevention. This work originated from a rigorous methodological process that integrates systematic reviews, expert consensus, and NUTRIGRADE-based evaluations to generate actionable recommendations. The updated definition of the MD extends beyond its nutritional aspects to embrace key sociocultural dimensions, such as culinary traditions, conviviality, and sustainability. This reconceptualization positions the MD as a holistic lifestyle model rather than a restrictive dietary pattern. It also reflects current scientific and public health priorities by explicitly excluding alcohol consumption, including red wine, from its core recommendations. This decision acknowledges growing evidence that even moderate alcohol intake increases the risk of cancer and cardiovascular disease. The MDGs addressed a broad spectrum of health outcomes. They highlighted varying degrees of positive association between adherence to MD and reduced incidence or mortality across different conditions. Adherence to the MD showed strong protective effects against cardiovascular and metabolic diseases. On the other hand, its association with oncological, neurocognitive, musculoskeletal, and autoimmune conditions appears to be positive, though supported by weaker evidence. Specific recommendations are tailored for different life stages and target groups, including children, pregnant women, older adults, and individuals with chronic conditions. Dissemination and implementation strategies emphasize integration into clinical care, schools, public policies, and digital health platforms. The MDGs provide a scalable and adaptable framework for national and regional adoption, promoting guideline harmonization. MD is thereby recognized as a pivotal public health tool in the face of global nutritional transitions and rising non-communicable diseases.